Dancing Sprites Above a Lightning Mapping Array—An Analysis of the Storm and Flash/Sprite Developments. Issue 20 (15th October 2021) - Tomicic, Maja; Soula, Serge; Defer, Eric; Prieur, Serge; Mlynarczyk, Janusz; Farges, Thomas; Chanrion, Olivier; Köhn, Christoph; Neubert, Torsten
Abstract: One of the most enigmatic types of sprites is the dancing sprite which appears to dance above the storm as sequential luminous emissions a few 100 ms or less apart. Dancing sprites occur in relatively small proportion and many aspects of their generation remain unknown. We present a multi‐instrumental analysis of a 20‐hr duration Mesoscale Convective System (MCS) over the northwestern Mediterranean Sea on September 21, 2019, that produced 21 sprites recorded with a video camera, of which 19 (90 % ) were dancing sprites. The asymmetric trailing stratiform MCS developed in strong convective conditions having a CAPE of 3, 500 J k g − 1 . It formed several convective cores (up to 2, 900 k m 2 with cloud top temperature < − 66 ° C) and exhibited a bow echo structure during the sprite production period. Using Lightning Mapping Array data, we show that the sprite producing positive cloud‐to‐ground (SP + CG) flashes mainly initiated at the edge of the convective line on the side of the stratiform region. The flashes propagated 100–200 km across it, producing both positive and negative CG strokes. The 19 dancing sprite events included 49 sequences, of which 46 were associated with distinct SP + CG strokes and 3 with surges during the continuing current. An especially bright and wide sprite sequence was produced by three distinct SP + CG strokes that occurred within 3 ms and spread over 54 km. This sprite sequence could be classified as a new sprite category resembling a "wall" but structured in three groups, each associated with one of the +CG strokes. Plain Language Summary: One of the most enigmatic types of sprites is the dancing sprite which appears to dance above the storm as sequential luminous emissions a few 100 ms or less apart. Dancing sprites occur in relatively small proportion and many aspects of their generation remain unknown. We present a multi‐instrumental analysis of a 20‐hr duration Mesoscale Convective System over the Mediterranean Sea on September 21, 2019, that produced 21 sprites, of which 19 were dancing. The storm developed in strong convective conditions and formed several convective cores with very high cloud‐tops and a bow‐echo structure. Most of the sprite producing flashes propagated from the convective to the stratiform region over long distances producing strokes of both polarity. The 19 events included 49 sprite sequences, of which 46 were associated with distinct strokes and 3 with surges during the continuing current. An especially bright and wide sprite was produced by three strokes that occurred within 3 ms and separated by 54 km and could be classified as a new sprite category. We accredit the high proportion of dancing sprites to a complex charge structure in the stratiform region with large potential and pockets of charge driving the leaders and allowing substantial discharge. Key Points: A high percentage (90 % ) of dancing sprites were produced by a large asymmetric MCS which developed in strong convective conditions over the Mediterranean Sea The sprite parent flashes mainly initiated at the edge of the convective region and propagated 100–200 km across the stratiform region An especially bright and wide sprite sequence was produced by three distinct positive CG strokes that occurred within 3 ms and were separated by 54 km